DISPUTES SETTLEMENT OF INDUSTRIAL RELATIONS IN INDONESIA - Syafii Syafii; M. Zamroni (Fakultas Hukum, Universitas Maarif Hasyim Latif, 2018)
Background of Studied In December 2003, Indonesia passed the final piece of legislation in its labour law reform program. One month later, this received presidential assent and was introduced as Act Number 2 of 2004 on Industrial Relations Disputes Settlement. To allow for the necessary preparations for the transition, this law came into effect in January 2006. This Act repealed the 1957 regulation on Industrial Dispute Settlement and Law Number 12 of 1964 on Termination in Private Enterprises, whereby disputes between workers and employers were to first be reported to the Ministry of Manpower and Transmigration .Under the former system, an officer from the the Ministry of Manpower and Transmigration would mediate the matter or refer it to compulsory arbitration by a Local Labour Dispute Resolution Committee. Appeals were then sent to the Central Labour Dispute Resolution Committee in Jakarta. These Committees consisted of the Ministry of Manpower and Transmigration officials, and representatives from employers and the AllIndonesia Workers’ Union. The Committees operated through an informal process, but had the authority to make legally binding decisions. There were no time limitations on the settlement of disputes before the Committees and individual workers did not have legal standing to bring individual disputes to the Committees. The Indonesian Minister of Manpower could veto all decisions. Disputes are to be resolved by a range of methods, including: · Bipartite negotiation; · Mediation; · Arbitration; · Determination by a panel of judges of the Industrial Tribunal; and · Appeals to the Supreme Court. ACT No.2 of 2004 Page | 18 The Industrial Dispute Settlement Law in its present form may go a long way to assisting in the development of a fair and effective labour dispute settlement system in Indonesia. Methodology of normative juridical deduction, the judicial approach.